Fluarix quadrivalent vaccine for influenza. (August 2015) - Graaf, Hans de; Faust, Saul N
<x xml:space="preserve">Abstract</x> Influenza A and B infections cause significant morbidity and mortality. Over the past 30 years, two main influenza B strains have been circulating globally. The trivalent influenza vaccine used in the last 25 years contains one B strain, with approximately 31% of B strain disease coverage over the last 10 years. Fluarix quadrivalent vaccine, containing two A and two B strains, combines the components of two existing trivalent vaccines to prevent this mismatch. This review gives an overview of the published data about Fluarix quadrivalent vaccines, showing an immunogenicity and safety profile of the vaccine comparable with the two licensed trivalent vaccines containing the same strains, but with no evidence for efficacy in the literature. Future vaccines aim for a universal influenza vaccine that will give a long-lasting protection against all influenza strains.